Perancangan Sistem Informasi Pemantauan Aktivitas Dan Dana Operasional (Sipanda) Di Pt. Sucofindo Cabang Jambi Berbasis Website - Hery Afriyadi; Nazwa Salsa Renata; Arya Ponco Saputra; Aditya Rahmattullah; Ahmad Azqi Yauci (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
PT SUCOFINDO Jambi Branch experienced challenges in monitoring operational costs due to limitations in the Oracle ERP Cloud system, which only provided portfolio-level cost analysis and lacked detailed tracking of fund allocations for individual order numbers. The use of alternative tools such as VBA Macro Excel, Google Sheets, and WhatsApp Bot created additional issues, including data duplication, file corruption risks, and difficulties in identifying cost components within revenue recognition accounts. This internship project aimed to develop SIPANDA (Operational Activity and Fund Monitoring Information System), a web-based application designed to improve the recording and monitoring of operational expenses. The system was developed using the Software Development Life Cycle (SDLC) Waterfall model, with PHP as the programming language and MySQL as the database platform. The implementation results showed that SIPANDA successfully automated data management through a smart bulk import feature integrated with an Anti-Duplicate algorithm and enabled real-time tracking of fund allocations for each order number. Furthermore, the application of Role-Based Access Control (RBAC) enhanced data security and integrity. Overall, SIPANDA reduced manual input errors, minimized data redundancy, accelerated financial reporting, and improved transparency in operational fund management, making it an effective solution to address the shortcomings of the previous system